2019
DOI: 10.3390/agronomy10010014
|View full text |Cite
|
Sign up to set email alerts
|

Plant Density Influences Reproductive Growth, Lint Yield and Boll Spatial Distribution of Cotton

Abstract: The number of cotton plants grown per unit of ground area has gained attention due to the high prices of inputs and lower production. Cotton yield per unit of area in Henan province has been stagnant in the last few years. The objectives of this study were to investigate cotton growth, yield, boll spatial distribution and biomass accumulation using different plant densities at cultivation and to find out the optimal plant density. A 2-year field experiment was conducted in a randomized complete block design un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…In a contrasting sorghum study by Villar et al (1989), increasing plant density from 16 to 38 plant m -2 reduced the days to flowering from 59 to 50 days. In cotton, high-density planting (11 plant m -2 ) slightly reduced flowering to 25-26 days from 26-31 days c with lower density planting (9 plant m -2 ) (Khan et al, 2017(Khan et al, , 2019.…”
Section: Density Of Plant Populationsmentioning
confidence: 96%
See 1 more Smart Citation
“…In a contrasting sorghum study by Villar et al (1989), increasing plant density from 16 to 38 plant m -2 reduced the days to flowering from 59 to 50 days. In cotton, high-density planting (11 plant m -2 ) slightly reduced flowering to 25-26 days from 26-31 days c with lower density planting (9 plant m -2 ) (Khan et al, 2017(Khan et al, , 2019.…”
Section: Density Of Plant Populationsmentioning
confidence: 96%
“…(1989), increasing plant density from 16 to 38 plant m ‐2 reduced the days to flowering from 59 to 50 days. In cotton, high‐density planting (11 plant m ‐2 ) slightly reduced flowering to 25–26 days from 26–31 days c with lower density planting (9 plant m ‐2 ) (Khan et al., 2017, 2019). The above studies suggest that genotype differences affect plant responses to high‐density planting under field conditions.…”
Section: Opportunities Of Speed Breeding Techniquesmentioning
confidence: 99%
“…The same authors added that cotton in narrow row spacing produced particular greater dry mass compared to the conventional system. Higher seed cotton yield was recorded in the narrow plant spacing compared to a wider spacing and increased bolls at the 1st, 2nd and 3rd positions of the plant with less yield and unnecessary vegetative growth that led to undesirable fruit shedding was observed in the wider spacing (Khan et al, 2020). Similarly, Clark and Carpenter (1992) reported higher seed cotton yield in narrow row spacing compared to wider inter row.…”
Section: Introductionmentioning
confidence: 91%
“…For instance, the plant density is 12.6 plants per m 2 in Georgia [113], 15.3 plants per m 2 in Louisiana [114], 6.6 plants per m 2 in Mississippi [115], and 10.0 plants per m 2 in Arizona [116]. In China, Khan et al [117] carried out a study using six different densities and stated that taller plants and a higher number of leaves per plant were obtained with cotton cultivated at a lower plant density, while, under a high plant density, a higher number of branches and fruiting nodes and a greater number of bolls per unit of soil area were observed. The authors further revealed that the highest seed cotton yield (4546 kg ha −1 ) and lint yield (1682 kg ha −1 ) were produced by "D5" (87,000 plant ha −1 ).…”
Section: Cotton Yield and Yield Components In Response To Plant Densitymentioning
confidence: 99%